(untitled) (REMUNOM, 2026)
Economic sanctions have been widely used as instruments of pressure in international relations, playing an important role in conducting foreign policy and imposing specific behaviors on nation states and economic agents. Although often justified as legitimate mechanisms for protecting political, economic, or international security interests, such measures can have significant legal effects, especially when they influence the formation of consent in business relationships that are already structured or in the process of being structured. Free consent is an essential element for the validity of legal acts, both in international law and in civil law, and is compromised when there is indirect imposition of will through economic coercion. In this context, this study aims to analyze the use of economic sanctions as an instrument of coercion in international law and examine their effects on the validity of legal transactions structured under this type of pressure. The research uses the deductive method, with a qualitative approach and bibliographic research technique, based on national and international doctrine. The results indicate that economic coercion can compromise the legal freedom necessary for the validity of consent, constituting a defect capable of invalidating legal and business acts. It is concluded that the use of economic sanctions, when used as a pressure mechanism, can have significant legal consequences, affecting the validity and legitimacy of relationships in business law at the global level. Keywords: Economic sanctions; Coercion; Contract law; Legal transaction; International law.